1983
DOI: 10.2172/6352309
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of radioactive-waste-treatment costs and the environmental impact of waste effluents in the nuclear fuel cycle: conversion of yellow cake to uranium hexafluoride. Part II. The solvent extraction-fluorination process

Abstract: HOTICf POBTIOHS OF TWS BEPOBT ARE IllECIBlETIt has been reproduced from the best available copy to permit the broadest possible availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Sidhu et al (2004) showed that radioactive Pu was removed from contaminated soil via extraction with hydrochloric acid, nitric acid, and citric acid, and the nuclear waste removal rates were as high as 90% [14]. Sear et al (1983) found that uranium removal was significantly improved with NaHCO 3 as the eluting agent [15]. In addition, bioremediation, including phytoremediation and microbial remediation, has been studied recently due to the low costs and feasibility for use in large polluted fields [16].…”
Section: Introductionmentioning
confidence: 99%
“…Sidhu et al (2004) showed that radioactive Pu was removed from contaminated soil via extraction with hydrochloric acid, nitric acid, and citric acid, and the nuclear waste removal rates were as high as 90% [14]. Sear et al (1983) found that uranium removal was significantly improved with NaHCO 3 as the eluting agent [15]. In addition, bioremediation, including phytoremediation and microbial remediation, has been studied recently due to the low costs and feasibility for use in large polluted fields [16].…”
Section: Introductionmentioning
confidence: 99%